Fish Passage Facilities Design Parameters for Connecticut River Dams: Holyoke Dam, Holyoke, Massachusetts - Rizzo, B (ScholarWorks@UMass Amherst, 1968)
None supplied. From introduction: The main purpose of this series of reports is to provide guidelines regarding engineering design parameters and functional design features for proposed anadromous fish passage facilities at existing dams on the Connecticut River. The anadromous fish species of main concern are American shad and Atlantic salmon. In order to pass the design fish population, upstream migrant facilities at Holyoke should consist of a barrier dam to divert fish into the tailrace area and a new fishway constructed at the Hadley Falls Station.